GAPO syndrome: a new syndromic cause of premature ovarian insufficiency. (1st November 2016) - Benetti-Pinto, C. L.; Ferreira, V.; Andrade, L.; Yela, D. A.; De Mello, M. P.
Abstract: Premature ovarian insufficiency has the following causes: genetic, autoimmune, metabolic, infectious, and iatrogenic dysfunctions (including radiotherapy, chemotherapy and surgery). However, premature ovarian insufficiency remains without a definite cause in a substantial number of cases. This article describes GAPO syndrome in association with premature ovarian insufficiency, as well as a novel ANTXR1 gene mutation. Histopathological study of the ovaries of a woman with hypergonadotropic hypogonadism revealed extensive deposition of hyaline extracellular material, with bilateral parenchymal atrophy and follicular depletion. Molecular study revealed a novel ANTXR1 gene mutation. The homozygous c.378 + 3A > G transition at the consensus donor splice site of intron 4 was identified. Our results support the involvement of ANTRX1 gene mutations in deregulated extracellular matrix. In addition, our study identified a novel ANTXR1 mutation causing GAPO syndrome, indicating it as a new cause of early loss of ovarian function.